1981
DOI: 10.1073/pnas.78.3.1878
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of formation of the esophageal carcinogen benzylmethylnitrosamine from its precursors by Candida albicans

Abstract: Previous studies in Linxian, an area of China with a high incidence of esophageal carcinoma, showed that fungal infections are common in the esophageal epithelium of patients with either premalignant changes or early esophageal carcinoma. Fungi of the genus Candida were the most frequent invaders. In these areas nitrate and nitrite are often present in high, concentrations in drinking. water and staple grains. The present studies have-established the ability of Candida albicana to augment the nitrosative forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 9 publications
2
33
2
1
Order By: Relevance
“…For example, iron deficiency may have an influence on the oral flora. It is well recognised that there exists a close association between the iron status of an animal and the microbiological flora (Weinberg, 1981) and recently it has been shown that Candida albicans, a commensal of the normal oral flora, can augment the carcinogenic potential of an oesophagus-specific carcinogen (Hsia et al, 1981). Indirect evidence in support of the importance of an altered flora is derived from the distribution palatal tumours in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…For example, iron deficiency may have an influence on the oral flora. It is well recognised that there exists a close association between the iron status of an animal and the microbiological flora (Weinberg, 1981) and recently it has been shown that Candida albicans, a commensal of the normal oral flora, can augment the carcinogenic potential of an oesophagus-specific carcinogen (Hsia et al, 1981). Indirect evidence in support of the importance of an altered flora is derived from the distribution palatal tumours in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…C. albicans as the major isolate is similar to previous studies which recorded similar observations on BQC. [10,12,35] C. tropicalis was isolated as a predominant isolate in OSF patients in samples collected from the tongue and buccal mucosa followed by C. albicans and C. krusei, which is in contrast to the previous studies. C. tropicalis shows the closest genetic similarity to C. albicans and exhibits similar phenotypic switching.…”
Section: Discussioncontrasting
confidence: 52%
“…[9][10][11] Oral submucous fibrosis (OSF), a chronic potentially malignant disorder, is of multifactorial origin with arecanut chewing as a predominant causative agent. [12] The tobacco contents (nicotine, polycyclic aromatic hydrocarbons, polonium, and nitrosoproline), which constitute as an additive component of betel quid, are reported to provide nutrition for Candida and promote their proliferation. [13] They may also increase the colonization of Candida by causing an increase in epithelial keratinization, decrease in salivary immunoglobulin A and leukocytic function, and oral epithelial changes such as atrophy, hyperplasia, and dysplasia which may compromise the epithelial integrity.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are better understood and probably result, at least in part, from CMC and the chronic mucocutaneous inflammation (especially esophagitis) it causes. 83 Enhanced IFN production is unlikely to play a direct role, as these cytokines have antitumoral activity. 84 Patients with esophagitis and dysphagia should be regularly screened for tumor by sequential biopsies of the esophagus.…”
mentioning
confidence: 99%